Association between IL-6 polymorphisms and Atopic Dermatitis in Chinese Han children - Huang, Shuangshuang; Wang, Hao; Zheng, Huiwen; Li, Wei; Shi, Jianrong; Shen, Chen; Tao, Ran (Frontiers in Pediatrics, 2023)
Atopic Dermatitis (AD) is a chronic inflammatory skin disease that affects almost 20% of children and 2–10% of adults worldwide. Previous studies revealed that Interleukin-6 (IL-6) plays an essential role in autoimmune and chronic inflammatory diseases. This study aims to investigate the associations between IL-6 polymorphisms and AD. Blood samples were collected from 132 AD patients and 100 controls, and single nucleotide polymorphisms (SNPs) in IL-6 (rs2069840 (C/G), rs2066992 (G/T), rs2069837 (A/G) and rs1800796 (G/C)) were analyzed using Multiplex PCR-Based Next Generation Sequencing (NGS). Results showed that the A/G genotype of IL-6/rs2069837 was significantly associated with a 1.933-fold increased risk of AD compared to those patients with A/A genotype (OR 1.933; 95%CI 1.086-3.438; p=0.024). The combined A/G-G/G genotype raised AD risk by 1.856 times compared to patients with the A/A genotype in dominant model (OR: 1.856; 95% CI: 1.056-3.261; p=0.030). No association was observed for 3 other SNPs and 4 haplotypes. These findings suggested that the A/G genotype of IL-6/rs2069837 was more susceptible to AD than A/A genotype in Chinese Han children, indicating the risk role of IL-6/rs2069837 in the occurrence of AD.